2015
DOI: 10.1002/berj.3183
|View full text |Cite
|
Sign up to set email alerts
|

‘Elite’ career‐changers in the teaching profession

Abstract: Evidence linking teacher quality and the ‘performance’ of education systems has led to a widespread emphasis on improving the quality of entrants to teaching. In the USA and UK particularly, policymakers have encouraged entrants who have been highly successful in other careers to switch to teaching, on the assumption that they bring distinctive attributes/competences that will not only enable them to become successful teachers, but to improve leadership and management cultures in schools. This study analyses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 43 publications
2
44
0
3
Order By: Relevance
“…The discourse of exceptionalism is explored in this study of 'elite career-changers' in ITE, for although studies have noted the 'added value' second-career teachers bring to the classroom (Mayotte 2003;Tigchelaar et al 2010), there is no compelling evidence of their impact on institutional practice or leadership culture from studies carried out in a wide range of contexts. The study reported here builds on an earlier study (hereinafter referred to as ECC1) of professionals who had successfully made the transition into teaching (Wilkins and Comber 2015). The most striking finding of this previous study was that despite strong evidence that resilience is a key attribute of career-changers, they are significantly less likely to complete their ITE programmes than 'first career' entrants.…”
Section: Introduction: Teacher Quality and System Qualitymentioning
confidence: 77%
See 4 more Smart Citations
“…The discourse of exceptionalism is explored in this study of 'elite career-changers' in ITE, for although studies have noted the 'added value' second-career teachers bring to the classroom (Mayotte 2003;Tigchelaar et al 2010), there is no compelling evidence of their impact on institutional practice or leadership culture from studies carried out in a wide range of contexts. The study reported here builds on an earlier study (hereinafter referred to as ECC1) of professionals who had successfully made the transition into teaching (Wilkins and Comber 2015). The most striking finding of this previous study was that despite strong evidence that resilience is a key attribute of career-changers, they are significantly less likely to complete their ITE programmes than 'first career' entrants.…”
Section: Introduction: Teacher Quality and System Qualitymentioning
confidence: 77%
“…The small number of studies focusing specifically on the motivation of individuals who have changed career to become teachers suggest they are similarly driven by social utility and intrinsic emotional satisfaction Some research has found a relationship between teacher recruitment levels and conditions in the wider economy (so impacting on graduate-level job security (Borman and Dowling 2008); the perception of teaching as a career that is virtually immune to economic context means that both recruitment and retention levels are increased during economic downturns. However, there is little or no indication in previous studies that this is a significant 'push' factor for career-changers; they are overwhelmingly 'pulled' by the perceived attractiveness of teaching as a career (Powers 2002;Anthony and Ord 2008;Wilkins and Comber 2015)…”
Section: Motivation To Teach?mentioning
confidence: 99%
See 3 more Smart Citations